A Three-level Space Vector PWM Strategy Based on Variable Virtual Middle Vector - LIN Zhenjun; LIU Yongjiang; LI Hua; LIU Haitao; LI Congda; XUE Xin (Kongzhi Yu Xinxi Jishu)
T-type three-level topology has been widely applied in power converters for its high efficiency and low output harmonics, and the performance of this converter is determined by the effect of its capacitor neutral point voltage control. This paper analyzed the neutral point voltage balance in T-type three-level circuit and proposed a variable virtual space vector PWM (VVSVPWM) strategy. By modulating the reference space vector using variable virtual middle vector which is constructed by plus or minus small vector and middle vector, the neutral point voltage has been effectively controlled. The feasibility and superiority of the T-type three-level topology applied on metro traction converter system has been verified by model simulation and experiments.